Gravity Probe B gyroscope readout system. (17th November 2015) - Muhlfelder, B; Lockhart, J; Aljabreen, H; Clarke, B; Gutt, G; Luo, M
Abstract: We describe the Gravity Probe B London-moment readout system successfully used on-orbit to measure two gyroscope spin axis drift rates predicted by general relativity. The system couples the magnetic signal of a spinning niobium-coated rotor into a low noise superconducting quantum interference device. We describe the multi-layered magnetic shield needed to attenuate external fields that would otherwise degrade readout performance. We discuss the ∼35 nrad/yr drift rate sensitivity that was achieved on-orbit.